FKEPG-LIMS : Fakulti Kejuruteraan Elektrik Kampus Pasir Gudang Lab Inventory Management System - Yasmin Abdul Rahman, Farah; Kasuan, Nurhani; Hisham Mat Saat, Ezril; Hasliza Abdul Rahman, Noor; Iqtiyan Ilham, Nur; Noor Suhana Jamil, Siti (International Journal of Engineering and Technology, 2018)
Information are the most valuable commodity in the modern era. In todayâ€™s lifestyle, society are virtually swarmed with a lot of Â Â Â Â Â Â Â Â Â Â Â information that cannot be misplaced or vanished. This study presents a development of web-based lab inventory management system that is used to record, manage and retrieve the lab equipment and components in Fakulti Kejuruteraan Elektrik Kampus Pasir Gudang namely FKEPG-LIMS. The main purpose of this study is to assist faculty members to view and keep track all the available lab Â Â Â Â Â Â equipment that have been purchased. The users can be classified as the Faculty Head, lab technicians, lecturers and students. The Â Â Â Â Â Â database is developed using MySQL and the HTML script written in PHP and Adobe Dreamweaver used design the web interface. The research has successfully demonstrated the feasibility of FKEPG-LIMS in managing and storing all the information. The stored Â Â Â Â Â Â Â Â information can also be retrieved, edited and deleted. The developed lab inventory management system will benefits users by providing fast and precise solution in inventory management.Â Â